2021
DOI: 10.1063/5.0061364
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter-resolution magnetic field imaging with digital micromirror device and atomic vapor cell

Abstract: Magnetic field source localization and imaging happen at different scales. The sensing baseline ranges from meter scale, such as magnetic anomaly detection, to centimeter scale, such as brain field imaging, to nanometer scale, such as the imaging of a magnetic skyrmion and single cell. Here, we show how an atomic vapor cell can be used to realize a baseline of 109.6 μm with a magnetic sensitivity of 10 pT/Hz1/2 @0.6–100 Hz and a dynamic range of 2062–4124 nT. We used a free induction decay (FID) scheme to supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, the fluxgate may be too large to be installed in miniature integrated atomic sensors. Because of this problem, some researchers proposed the realization of in-situ measurement of the coil magnetic field using the atomic spin effect [18]. Zhang et al calibrated the coil magnetic field via extraction and analysis of the Larmor precession frequency of hyperpolarized 3 He in an atomic magnetometer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fluxgate may be too large to be installed in miniature integrated atomic sensors. Because of this problem, some researchers proposed the realization of in-situ measurement of the coil magnetic field using the atomic spin effect [18]. Zhang et al calibrated the coil magnetic field via extraction and analysis of the Larmor precession frequency of hyperpolarized 3 He in an atomic magnetometer [19].…”
Section: Introductionmentioning
confidence: 99%
“…A high measurement bandwidth was obtained whilst maintaining good sensitivity in a continuous sampling mode; this was helpful for further applications in magnetometers or sensor arrays with high measurement bandwidth requirements. H. F. Dong et al [ 21 ] demonstrated a distributed magnetic field measurement scheme based on FID magnetometer. The magnetic sensitivity reached 10 pT/ in a bandwidth of 0.6–100 Hz.…”
Section: Introductionmentioning
confidence: 99%